Breast Cancer Management: Present Scenario (Medical Journal of Indonesia, 2007)
The treatment management of breast cancer is perhaps the most controversial of all and has evolved a sea change over the years. Contrast enhanced MRI imaging is emerging as the most efficient imaging diagnostic tool. Newer approaches for the biopsy of inoperable breast cancer are aimed at obtaining diagnostically adequate tissue samples while minimizing invasiveness and the risk of complications. The regional vigour that Halsted followed rigorously, albeit, achieved significant locoregional control, could not lead to improved long-term survival. With the passage of time, people have understood the systemic nature of the disease and the paramount need to incorporate systemic treatment even in relatively earlier stages and curtain surgical ablative techniques. The role of primary systemic therapy in the management of breast cancer is fast emerging as a vital option. In HER 2/neu gene overexpressed patients, addition of trastuzumab to the systemic treatment is a distinct improvement in overall survival. (Med J Indones 2007; 16:55-60) Keywords: breast cancer, tumour, chemotherapy, radiotherapy, systemic therapy